Factors associated with childhood pneumonia and care seeking practices in Nepal: further analysis of 2019 Nepal Multiple Indicator Cluster Survey - Sunita Dharel; Binjwala Shrestha; Prem Basel (BMC, 2023)
Abstract Background Acute Respiratory Infection (ARI) is still a major public health problem in Nepal. The prevalence of ARI among under five children was 2.1% in 2019 and many children from marginalized families suffer disproportionately and many of them die without proper care and treatment. The objective of this study was to identify factors associated with childhood pneumonia and care-seeking practices in Nepal. Methods This was a secondary analysis of the Nepal Multiple Indicator Cluster Survey (MICS) 2019, which uses multi-stage Probability Proportional to Size sampling. Data from 6658 children were analyzed using SPSS 22. Chi-square test and logistic regression analysis were conducted with odds ratio and its corresponding 95% confidence interval after adjusting for confounders. Results Children aged 0 to 23 months had1.5 times higher odds of pneumonia compared to the age group 24 to 59 months (AOR = 1.5, CI 1.0-2.3) and children from rural area had 1.9 times the odds of having pneumonia than urban children (AOR = 1.9, CI 1.2-3.2). Underweight children had 2.3 times greater odds of having pneumonia than normal weight children (AOR = 2.3, CI 1.4-3.9). The odds of having pneumonia were 2.5 higher among children of current smoking mothers compared those with non-smoking mothers (AOR = 2.5, CI 1.1-5.7). Similarly, children from disadvantaged families had 0.6 times protective odds of pneumonia than children from non-disadvantaged families (AOR = 0.6, CI 0.4-1.0). Only one quarter of children received treatment from public facilities. Of those who received treatment, nearly half of the children received inappropriate treatment for pneumonia. One in ten children with pneumonia did not receive any kind of treatment at all. Conclusions Pneumonia is still a public health problem in low-income countries. Public health program and treatment services should be targeted to younger children, careful attention should be given to underweight children, and awareness and nutrition related activities should be focused on rural areas. Addressing inequity in access to and utilization of treatment of childhood illnesses should be prioritized. Keywords: Childhood pneumonia, epidemiology, health care seeking behavior, Nepal.